European Soccer Championship Results: Since 1958 - Malolepszy, Tomasz (Rowman & Littlefield Publishers, 2013)
During the 2012 European Soccer Championship (popularly called the “Euro”), nearly one and a half million people attended the matches. It was the third most-watched sporting event in the world, with the best teams on the continent competing for the title. Yet, only half a century ago the idea of a European championship wasn’t widely supported. When it finally received the green light from the world soccer authorities, the best European teams weren’t interested in participating in the new event. But as the popularity of soccer grew across the world, and the reputation of the tournament increased with each competition, the Euro has become one of the most popular sporting events world-wide. In European Soccer Championship Results: Since 1958, Tomasz Malolepszy charts the growth and expansion of this popular sport in Europe with a complete statistical history of both the men’s and women’s competition. For the first time ever, soccer fans can find detailed results, rosters, medalists, and standings for the European Championships all in a single volume. In addition, this book contains a list of interesting records, many of which have never before been published. European Soccer Championship Results is a valuable resource for any soccer fan, journalist, or researcher. Companion volumes to this book include European Basketball Championship Results: Since 1935, European Ice Hockey Championship Results: Since 1910, and European Volleyball Championship Results: Since 1948.